Efforts of Akidah Akhlak Teachers in Instilling the Values of Amar Ma’ruf Nahi Munkar at Assiham Quran School Bandar Lampung - Widodo Prasetyo; Ahmad Zumaro; Septa Ahmad Santoso (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
Character education is an important aspect in shaping an intelligent generation with integrity and moral values. From an Islamic perspective, character education is based on the values of amar ma'ruf nahi munkar, which teach the community to promote good and prevent evil. This study aims to identify the efforts of Akidah Akhlak teachers in instilling the values of amar ma'ruf nahi munkar in students at Sekolah Quran Assiham Bandarlampung, as well as the factors influencing its success. The method used is a descriptive qualitative approach, with data collection techniques through semi-structured interviews and direct classroom observations. The results of the study indicate that teachers’ efforts in instilling the values of amar ma'ruf nahi munkar include teaching, habituation, and role modeling. Influencing factors include the teacher's role, student character, facilities and infrastructure, and the surrounding environment. Although there are challenges, such as students' varied characteristics and environmental influences, the learning outcomes still show positive development in instilling these values. This study suggests the need for collaboration between teachers and parents, as well as the enhancement of supporting facilities to strengthen character education in schools.